Susceptibility Pattern of Neisseria gonorrhoeae towards Cefixime and Ceftriaxone using Kirby-Bauer Method in Dr. Saiful Anwar General Hospital Malang - Lita Setyowatie; Tantari SHW; Inneke Yulian (Faculty of Medicine, Universitas Airlangga, 2020)
Background: Gonorrhea remains the second most common sexually transmitted infection (STI) in the world with an increasing number of cases. Oral cefixime and IM ceftriaxone are still the mainstay therapy for gonorrhea in Indonesia. However, previous studies suggested possible resistance to ceftriaxone and cefixime, which are the first-line treatment of gonorrhea. To date, there are no data available regarding the susceptibility of these antibiotics for the treatment of gonorrhea in Dr. Saiful Anwar General Hospital (RSSA) Malang. Purpose: Determine susceptibility pattern of Neisseria gonorrhoeaetowards cefixime and ceftriaxone in RSSA Malang. Methods: The samples were patients of the Outpatient Clinic of Dermatology and Venereology Department with a symptom of discharge which contained Gram-negative diplococcus after Gram staining and had a positive culture of Neisseria gonorrhoeae. Susceptibility testing for cefixime and ceftriaxone antibiotics were performed using the Kirby-Bauer method. The data are presented in percentages. Result: Antibiotic susceptibility test results showed that 80.77% of Neisseria gonorrhoeaeisolates were still susceptible to cefixime, and 80.77% of isolates were still susceptible to ceftriaxone. Conclusion: Cefixime and ceftriaxone are still effective as gonorrhea therapy in RSSA Malang.